Lung cancer, stomach cancer, and smoking status among coal miners. A preliminary test of a hypothesis. - Ames, R G; Gamble, John F (Scandinavian Journal of Work, Environment & Health, 1983)
This paper presents an empirical test of the hypothesis of Meyer et al, who propose inhaled carcinogens to be a risk for both stomach and lung cancer, stomach cancer occurring in persons with nonimpaired lungs and lung cancer occurring in persons with impaired lungs. Based upon a case-referent study comparing 46 white male coal miners who died from stomach cancer in the United States with age-matched miners who died from lung cancer and with reference miners who died from other cancers or from noncancer, nonaccident causes, the present study failed to confirm the Meyer hypothesis. The data suggest a reverse relationship than that postulated, namely, that airway obstruction may be a precondition for stomach cancer and normal pulmonary function a precondition for lung cancer. Different dust agents were found to be involved with cancers at the different sites. For coal miners with airway obstruction, greater years of coal mine dust exposure were found to pose a slightly elevated stomach cancer risk (odds ratio 3.64, not significant), while, for miners with normal ventilatory function, cigarette smoking posed a disproportionately elevated lung cancer risk (odds ratio 7.00, not significant).